Four Dimensions of Diamond T: Combination Trade Marks of Colours And Shapes - McGowan, Michael (Victoria University of Wellington Law Review, 2006)
This article examines the relatively new fields of colour and shape trade marks. It was initially feared by some academics that the new marks would encroach on the realms of patent and copyright. However, the traditional requirements of trade mark law, such as functionality and descriptiveness, have meant that trade marks in colour and shape are extremely hard to acquire if they do not have factual distinctiveness. As colour and shape trade marks have no special restrictions, it is proposed that the combination trade mark theory and analysis from the Diamond T case should be used as a way to make them more accessible. The combination analysis can be easily applied because every product has a three dimensional shape and a fourth dimension of colour.